Study on protein profiling of slaughtered and stunned chicken in preparation for rapid test kit development - Norshahida binti Abu Samah (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Stunning is a process where chickens are paralyzed by mild electrical treatment prior to exsanguinations. Such treatment is economic wise and efficient especially in mass production of slaughtered chicken. However, the stunning process needs to be monitored in order to confirm that the chickens are still alive when slaughtering takes place. In Malaysia, The National Fatwa Committee has decided that water bath stunning is allowed in poultry slaughtering provided that the current used must be in the range of 0.25 A to 0.5 A. In this study, the relationship between stunning parameters and protein expression was analyzed by Design Expert Software Version 6.0.8. The stunning parameters studied are current (0.25 A, 0.5 A, 0.75 A) and voltage (10 V, 40 V, 70 V). A simple and reliable method using proteomics approach was employed. Two-dimensional (2D) protein profiles were analyzed by ImageMaster 2D Platinum 6.0 software to identify potential biomarkers in differentiating the over stunned chicken from the standard stunned and religious slaughtered chicken. This study is in line with the understanding on the nature of proteins which are dynamic and responsive to both internal and external stimuli. Thus, electrical treatment of stunning is considered as one type of external stimuli to the chicken, thereby, expecting it to cause changes in the level of protein expression. It was observed that the protein intensity is increasing as the current and voltage increased. The potential biomarkers discovered through 2D gel electrophoresis were identified by MALDI-TOF mass spectrometer and further verified at the transcriptional level by Real Time PCR. The potential biomarkers identified in this study are Troponin I, Actin Alpha Cardiac Muscle 1, Muscle Creatine Kinase (M-CK), Aldolase A, Voltage-dependent Anion Channel 2, Actin Related Protein 2 Homolog (ARP2), Aldolase C and Enolase 1. Three of these proteins were only detected in over stunning treatment of 0.75 A, 70 V which are Aldolase A, ARP2 and Enolase 1. The rest of the proteins could be detected at current of 0.5 A and some even at 0.25 A, but they are completely absent in 0 A, 0 V non stunned chickens. These proteins could be developed as biomarkers after optimization of antigen-antibody specific reaction by determining a specific threshold for the over stunned expression. Upregulation of genes for the protein biomarkers confirmed that electrical treatment in stunning alters the expression and protein constituents of the chickens. The highest gene upregulation was detected in ARP2 with 1086 while the lowest is M-CK with a fold change of 4.7. These identified proteins are highly beneficial for development of detection kit for halal slaughtered chicken. Then, over stunned chicken will be identified even if they are already in market.